2008
DOI: 10.1111/j.1462-5822.2008.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of innate immune cell functions by theBurkholderia cepaciacomplex:Burkholderia cenocepaciabut notBurkholderia multivoransdisrupts maturation and induces necrosis in human dendritic cells

Abstract: SummaryBurkholderia cepacia complex (BCC) bacteria cause pulmonary infections that can evolve into fatal overwhelming septicemia in chronic granulomatous disease or cystic fibrosis patients. Burkholderia cenocepacia and Burkholderia multivorans are responsible for the majority of BCC infections in cystic fibrosis patients, but B. cenocepacia is generally associated with a poorer prognosis than B. multivorans. The present study investigated whether these pathogens could modulate the normal functions of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
(110 reference statements)
2
13
0
Order By: Relevance
“…After 7 days of incubation, including one complete replacement of media, at 37 uC in a 5 % CO 2 atmosphere, cells were removed from plates by gentle scraping and cells with an immature DC phenotype were confirmed by flow cytometry as detailed below. In concordance with other studies, cells were .95 % pure (MacDonald & Speert, 2008;Noske et al, 2009). …”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…After 7 days of incubation, including one complete replacement of media, at 37 uC in a 5 % CO 2 atmosphere, cells were removed from plates by gentle scraping and cells with an immature DC phenotype were confirmed by flow cytometry as detailed below. In concordance with other studies, cells were .95 % pure (MacDonald & Speert, 2008;Noske et al, 2009). …”
Section: Methodssupporting
confidence: 78%
“…Meanwhile, imipenem is lipid insoluble and penetrates cells poorly if at all (Menashe et al, 2008;Murdoch & Peterson, 1991;Sahly et al, 2008). Numerous other studies have used imipenem (Boddey et al, 2007;Brown et al, 2004;MacDonald & Speert, 2008) rather than kanamycin. We have compared the effects of Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is clear that members of the BCC can induce immune responses in cultured mammalian cells (12,54,(60)(61)(62)(63) (Fig. 6), there is much less known regarding the host immune responses in vivo to this group of organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity for intracellular replication of B. cenocepacia in eukaryotic cells and the factors involved in bacterial survival remain unclear. Some studies have reported that B. cenocepacia and other Bcc strains can replicate inside eukaryotic cells (6,31,36,40,46,47,59) while others have shown minimal to no replication (29,30,39,45) (Table 1 summarizes intracellular survival/replication assays with Burkholderia species in phagocytic cells of mammalian origin). These discrepancies could be due to variations in the experimental procedure, including differences in eukaryotic cell types and Bcc strains, and the method for quantification of intracellular replication.…”
mentioning
confidence: 99%